2021
DOI: 10.1002/ange.202106046
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Stereoselective Cascade of β,γ‐Unsaturated Ketones by Dipeptided Phosphonium Salt Catalysis: Stereospecific Construction of Dihydrofuro‐Fused [2,3‐b] Skeletons

Abstract: Chiral (dihydro)furo‐fused heterocycles are significant structural motifs in numerous natural products, functional materials and pharmaceuticals. Therefore, developing efficient methods for preparing compounds with these privileged scaffolds is an important endeavor in synthetic chemistry. Herein, we develop an effective, modular method by a dipeptide‐phosphonium salt‐catalyzed regio‐ and stereoselective cascade reaction of readily available linear β,γ‐unsaturated ketones with aromatic alkenes, affording a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Noteworthy, Wang's group recently disclosed an unprecedented asymmetric dearomative [3+2] cycloaddition of 2‐nitrobenzofurans/benzothiophenes or 2‐nitroindoles with β,γ‐unsaturated ketones 70 under the catalysis of dipeptide‐phosphonium salt C24 in an exclusive α‐selective pathway, involving the cascade Michael addition followed by the intramolecular O ‐substitution, affording the cycloadducts 71 – 73 in remarkable yields with outstanding diastereo‐ and enantioselectivities (Scheme 27). [46] The deep control experiments by using the Me‐protecting phosphonium salts C24−Me in this transformation showed inferior enantiocontrols, implying the pivotal role of H‐bonding effects in the enantio‐induction process. Density functional theory calculations unambiguously revealed that the excellent regioselectivity was determined by the lower reaction energy barrier resulted from the α‐selective attack to the nitrobenzofurans compared with the γ‐selective pathway.…”
Section: Asymmetric Dearomative Annulations With 2‐nitrobenzofurans A...mentioning
confidence: 91%
“…Noteworthy, Wang's group recently disclosed an unprecedented asymmetric dearomative [3+2] cycloaddition of 2‐nitrobenzofurans/benzothiophenes or 2‐nitroindoles with β,γ‐unsaturated ketones 70 under the catalysis of dipeptide‐phosphonium salt C24 in an exclusive α‐selective pathway, involving the cascade Michael addition followed by the intramolecular O ‐substitution, affording the cycloadducts 71 – 73 in remarkable yields with outstanding diastereo‐ and enantioselectivities (Scheme 27). [46] The deep control experiments by using the Me‐protecting phosphonium salts C24−Me in this transformation showed inferior enantiocontrols, implying the pivotal role of H‐bonding effects in the enantio‐induction process. Density functional theory calculations unambiguously revealed that the excellent regioselectivity was determined by the lower reaction energy barrier resulted from the α‐selective attack to the nitrobenzofurans compared with the γ‐selective pathway.…”
Section: Asymmetric Dearomative Annulations With 2‐nitrobenzofurans A...mentioning
confidence: 91%
“…65 In 2021, Wang's group's documented α-addition of β,γ-unsaturated ketones triggered a multistep-proceeding cascade with nitro-substituted aromatic alkenes that included 2-nitroindoles, 2-nitrobenzofurans, and 2-nitrobenzothiophenes (Scheme 50). 66 Under the catalysis of chiral amino acid-derived bifunctional phosphonium salt C31, the reaction furnished three types of dihydrofuro-fused [2,3-b] architecture 213 with excellent yields (90-99%) with perfect diastereo-and enantioselectivities (all cases >20 : 1 dr, 90->99% ee). In their proposed reaction cycle (simplified cycle as shown in The direct asymmetric α-functionalization of β,γ-unsaturated carboxylic acids has been a focus in organic synthesis and medicinal chemistry, and many research breakthroughs have been made over the past decade.…”
Section: Unsaturated Aldehydesmentioning
confidence: 99%
“…14 However, compared with the development of most one-step methods, general and effective cascade protocols for the reaction of the β,γunsaturated carbonyl compound are very limited, 15 1, path a). 16 In this Letter, we outline the design of a new type of phosphonium-catalyst-guided, γ-addition-driven C2-involved cascade of β,γ-unsaturated ketones with 1,4-conjugated systems such as ortho-quinone methides (o-QMs), which allows rapid stereoselective access to structurally fused 1,3-dioxolochromans (Figure 1b). 17 We expect that this catalytic γ-addition-driven C2-involved cascade process will also provide a valuable platform for the development of an effective and practical asymmetric cascade protocol toward diverse transformations of deconjugated β,γ-unsaturated carbonyl compounds.…”
mentioning
confidence: 99%
“…The mechanism of this cascade reaction was not rigorously discussed in this stage, and we prefer that the reaction follows a stepwise mechanism that was also described in the literature. 16 The deuterium-labeling experiment was also performed, and deuterium incorporation into both the αand γ-positions of the product (d-3a) was observed with the addition of 5.0 equiv of CD 3 OD (Figure 2A). The result indicated the possibility of anionic intermediates In-A and In− B/In-C in the reaction system.…”
mentioning
confidence: 99%